A history of Hittite literacy - Hout, Theo van den, 1953- (Cambridge)
xxvi, 427 sayfa
Keywords: “Why did the Anatolians remain illiterate for so long, although surrounded by people using script? Why and how did they eventually adopt the cuneiform writing system and why did they still invent a second, hieroglyphic script of their own? What did and didn't they write down and what role did Hittite literature, the oldest known literature in any Indo-European language, play? These and many other questions on scribal culture are addressed in this first, comprehensive book on writing, reading, script usage, and literacy in the Hittite kingdom (c.1650–1200 BC). It describes the rise and fall of literacy and literature in Hittite Anatolia in the wider context of its political, economic, and intellectual history“ --